Os dissonantes mundos de Rubem Fonseca em Axilas e outras histórias indecorosas - Vizentin, Alana (2013)
Rubem Fonseca is an important author on the national literary scene, his production crosses four decades representing the controversial issues of the contemporary times and of this experiences protagonists. His choking and brutal themes focus marginal and transgressor universes; his books are known by the brutality of its representation. The eighteen short stories in Axilas e outras histórias indecorosas are constitute as a literary representation of the conflicting relations that are established among subjects in contemporary. The present dissertation aims to investigate how the author portrays in his short stories the contemporary living between so different subjects that intersect, collide and somehow reflects on the narrative the symptoms of a system in economic and affective decadence of the actual global system. Our interest is to investigate how the author s narrative has been changing through these four decades, with themes already known on the author s narratives and how these short stories follow the contemporary world and the human insert on this context changes. For this reading were chosen, specially, the studies of Octavio Ianni, Fredric Jameson, Homi K. Bhabha, Zigmunt Bauman, Stuart Hall and Eric Landawsky.